Dynamics of attack actions in the mobbing strategy: The case of Lithuania - Zukauskas, Pranas; Vveinhardt, Jolita; Melnikas, Borisas; Grančay, Martin (Journal of Business Economics and Management, 2015)
The purpose of this research is to determine the occurrence and prevalence of different mobbing actions used against a victim in the context of Lithuanian organisations, taking into account the type of professional activity.A questionnaire was created for the purpose of the research. The reliability of the ques- tionnaire is demonstrated using indicators of the methodological quality of characteristics. The research revealed that in mobbing strategies, most bullying behaviour is interrelated and constructs a particular system, which is driven by insulting communication, defama- tion and isolation.The results draw the attention of managers of organisations to the nature of unethical communication and the need to protect dignity and reputation of employees and prevent mobbing and bullying.An original instrument was developed and used to interview mobbing and bullying vic- tims.